Evaluasi Implementasi Tahap Awal Program Pendidikan Sekolah Rakyat di SRMA 19 Bantul - Wahyu Insani; Suwadi Suwadi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2026)
In this study, the CIPP (Context, Input, Process, Product) evaluation model was used to assess the implementation of the People's School Education Program in its early stages. People's schools are an alternative education method designed to improve access to education for vulnerable socioeconomic groups. This study employed a descriptive qualitative methodology and employed a case study design. Data were collected through analysis of institutional documentation and in-depth semi-structured interviews with educators and administrators directly involved in program implementation. The four main components of the CIPP model were used to analyze the obtained data thematically. The results indicate that the program has been contextually designed to meet the needs of the target community. In terms of input, the program is supported by institutional commitment to implementation, although there are still limitations related to learning facilities and the availability of human resources. In terms of process, program activities are implemented adaptively, and in terms of product, initial progress is seen in increasing learning motivation and strengthening student character. Overall, the findings of this study demonstrate progress in the early stages of implementation and suggest that ongoing evaluation is needed to support program refinement and sustainability.